1981
DOI: 10.2307/3280780
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Basis of Eimeria tenella-Induced Mortality in Individual Chickens

Abstract: Chickens dying from Eimeria tenella infection revealed four major physiological stresses before death: (1) hypothermia, (2) depletion of carbohydrate stores, (3) metabolic acidosis, and (4) renal tubule-cell dysfunction. These stresses were less pronounced in chickens surviving the infection. Similar stresses could not be demonstrated in pair-feeding trials, in which uninfected chickens were fed only the amount consumed by infected chickens. Prolonged starvation of uninfected chickens only slightly altered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

1982
1982
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
1
4
0
3
Order By: Relevance
“…These results of our study confirmed the studies [19] and [18]. [20] and [21] consider the bill as an important part of the body for the assessment of bird thermal status. Authors [12] notice, that also shank as un-feathered part of bird body is suitable for evaluation of thermal status of birds.…”
Section: Discussionsupporting
confidence: 82%
“…These results of our study confirmed the studies [19] and [18]. [20] and [21] consider the bill as an important part of the body for the assessment of bird thermal status. Authors [12] notice, that also shank as un-feathered part of bird body is suitable for evaluation of thermal status of birds.…”
Section: Discussionsupporting
confidence: 82%
“…Bu düşüşlerle ilişkili olarak ilacın plazma proteinlerine bağlanma oranı düşmüş ve böylece kanda bulunan serbest sülfakinoksalin yoğunluğunda artış şekillenmiştir. Koksidiyoz olgularında hayvanların böbrek fonksiyonlarının bozulabileceğine ilişkin veriler bulunmakla birlikte 22,36 Yapılan bu çalışmada, ilacın kursak içi verilme durumunda etkili kan yoğunluğunu sürdürme süresi sağlıklı hayvanlarda 24 saat iken, koksidiyozlu hayvanlarda bu süre 18 saate düşmüştür. Bu düşüş, ilacın kursak içi belirtilen dozlarda aynı sıklıkla kullanılmayacağını gösterse de koksidiyozun sağaltımında bu yöntemin pratikte kullanımı söz konusu değildir.…”
Section: Tartışma Ve Sonuçunclassified
“…Bu düşüşlerle ilişkili olarak ilacın plazma proteinlerine bağlanma oranı düşmüş ve böylece kanda bulunan serbest sülfakinoksalin yoğunluğunda artış şekillenmiştir. Koksidiyoz olgularında hayvanların böbrek fonksiyonlarının bozulabileceğine ilişkin veriler bulunmakla birlikte 22,36 , bu durum ilacın atılımındaki artışı tam olarak engelleyememektedir. Bu olayda, böbrek hasarının çok ileri derecede olmamasının da etkisi söz konusudur.…”
Section: Tartışma Ve Sonuçunclassified
“…Ces résultats sont conformes à la description par Y VOR É et al (1972) des effets de la maladie. Par comparaison avec l'effet d'autres types de coccidiose (W ITLOCK et al, 1981 ;W ITLOCK , 1984), on n'observe pas ici de diminution des réserves glucidiques. L'estérase plasmatique est très significativement augmentée chez les animaux inoculés par rapport aux témoins.…”
Section: A Effet Global Du Traitementunclassified